Hubungan Antara Panjang Lingkar Lengan Atas (LILA) dengan Kadar Hemoglobin ( Hb) pada Ibu Hamil di Wilayah Puskesmas Purwokerto Selatan - Aisah Oktaviani; Devita Elsanti (Jurnal Keperawatan Muhammadiyah, 2020)
Objective: To determine the correlation between upper arm circumference length (LILA) and hemoglobin (Hb) levels in pregnant women in the work area of Public Health Care Center of Purwokerto Selatan. Method: The is a quantitative research with descriptive analytic methods using a cross sectional approach. The sample technique used is cluster random sampling with 94 respondents. Results: It was found that the age of most respondents or 43 respondents (45.7%) were 26-35 years old, the most respondents or 44 (46.8%) were graduated from SMA (Senior High School), the parity of most respondents or 67 (71.3%) is multigravida, most respondents or 87 (92.6%) were housewives. Most respondents or 74 (78.7%) had normal upper arm circumference (LILA) which had a length of 23.5 cm. Most respondents had a normal hemoglobin level of 48 (51.1%) with a hemoglobin level of 11 gr / dL. The Spearman Rank test results obtained p value of 0.0001.